M is for Married - 13 Erotic Short Stories - B., Malva (Saga Egmont, 2023)
'M is for Married - 14 Erotic Short Stories' is a collection of erotica that will make you want to say 'I do' to pleasure. From consummating a marriage during a desire-filled honeymoon to the illicit infidelity of married couples, this collection has a sexy story for every reader.